2011
DOI: 10.1177/1010539511409923
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Active Life Expectancy Among Older Thais

Abstract: This study aims to determine the disability prevalence and changes in active life expectancy of the Thai older people between 1997 and 2004. Data on disability of older people aged ≥60 years were obtained from the National Health Examination Surveys. Disability refers to one or more restrictions on the activities of daily living. The Sullivan method was used to calculate active life expectancy. A total of 4048 older people in 1997 and 19 372 older people in 2004 were included in the analysis. Active life expec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…In general, gender differences are largely due to mortality differences favoring women, rather than differences in the onset of disability [ 30 ]. Higher disability prevalence among women may be a function of longer survivorship in disability rather than higher incidence of disability [ 31 , 32 ], in that women have higher prevalence of nonfatal but disabling diseases and men have higher prevalence of fatal diseases and chronic diseases strongly related to mortality [ 22 ]. Chang et al [ 31 ] ascribed Japanese women disadvantage in disabilities to gender inequalities in socioeconomic status and disease profiles.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, gender differences are largely due to mortality differences favoring women, rather than differences in the onset of disability [ 30 ]. Higher disability prevalence among women may be a function of longer survivorship in disability rather than higher incidence of disability [ 31 , 32 ], in that women have higher prevalence of nonfatal but disabling diseases and men have higher prevalence of fatal diseases and chronic diseases strongly related to mortality [ 22 ]. Chang et al [ 31 ] ascribed Japanese women disadvantage in disabilities to gender inequalities in socioeconomic status and disease profiles.…”
Section: Resultsmentioning
confidence: 99%
“…Overall, the gender paradox is widely acknowledged and validated across different studies set in different countries, both high income and low and middle income countries (LMIC). For example, some of the results from our literature review showed evidence of the gender paradox in Brazil[ 27 , 29 , 37 39 ], Mexico[ 40 ], Hong Kong[ 41 ], Japan[ 31 , 36 , 42 , 43 ], Singapore[ 44 ], China[ 45 – 50 ], Bangladesh[ 23 ], Thailand[ 32 , 34 , 51 – 53 ], United States[ 22 , 30 , 54 ], Denmark[ 55 57 ], England[ 58 , 59 ], Italy[ 25 , 60 ], Bulgaria[ 61 ], Turkey [ 62 ], France[ 14 , 63 , 64 ] and across Europe [ 33 , 65 68 ].…”
Section: Resultsmentioning
confidence: 99%
“…Many theories have been proposed to explain the ‘gender paradox’ in mortality and disability, among which the most prevalent is that women may have higher prevalence of nonfatal but disabling diseases and men have higher prevalence of fatal and chronic diseases strongly related to mortality. Some researchers [5, 6] hypothesize that higher disability prevalence among women may be a function of longer survival in disability rather than higher incidence of disability.…”
Section: Introductionmentioning
confidence: 99%
“…Our findings indicate that the prevalence of ADL limitations increased with age. Similarly, a previous study [24] reported that the prevalence of disability increased with older age. Older people presented a higher prevalence of functional limitations than younger people.…”
Section: Main Findings Interpretations and Comparisons With Related S...mentioning
confidence: 54%